PENGARUH PENGELUARAN PEMERINTAH, PENANAMAN MODAL ASING (PMA) DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI KALIMANTAN BARAT - B1011131103, Sadeli (Jurnal Pembangunan dan Pemerataan, 2017)
This study aims to identify and measure the size of government spending, foreign direct investment (FDI) as well as local revenues to economic growth of the district / city in West Kalimantan. The data used in this research is secondary data (panel data) collected from the publication of the Central Statistics Agency of West Kalimantan from 2010 to 2014.The analytical method used in this research is multiple regression analysis with Random Effect models done by the application of E-Views 8. Of the three independent variables, which have a significant influence on the dependent variable only two variables: foreign direct investment (FDI) and the positive effect local revenues significantly and positively and significantly. While government spending variables did not significantly affect the economic growth of the district / city in West Borneo from 2010 to 2014.Keywords: Economic